Veřejnost jako cílový objekt public relations - Jelínek, Radim (Univerzita Pardubice, 2000)
The article deals with aiming groups of public as an aiming object of public relations. Attention is paid to two basic dividing of aiming groups - dividing according to sociodemohraphic coefficients and dividing from the point of view of relationship between public and firm. There is also characterized their development. The necessity of combination of the both of dividing is referred to at the end of the article.
Keywords: veřejnost; Public relations; sociální skupiny; veřejné mínění